Diffusion and Relaxation Kinetics of Chitosan-graft-poly (Acrylic Acid) Hydrogels: A Theoretical and Experimental Study - Jayanudin, Jayanudin; Lestari, Retno S. D.; Barleany, Dhena Ria; Pitaloka, Alia Badra; Yulvianti, Meri; Prasetyo, Dimas (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
Hydrogels, as three-dimensional polymer networks, are extensively utilized due to their ability to absorb significant amounts of water while remaining insoluble. Chitosan-grafted poly(acrylic acid) hydrogels, in particular, combine high water absorption with improved mechanical properties, making them ideal for applications in agriculture and drug delivery. This study investigates the swelling kinetics of chitosan-graft-poly(acrylic acid) hydrogels synthesized with varying concentrations of the crosslinker N,N'-methylenebisacrylamide (MBA). The objective is to establish the relationship between crosslinker concentration and hydrogel performance by evaluating their swelling behavior using kinetic models. The hydrogels were prepared via free-radical polymerization, with MBA concentrations of 0.015 g (Hgel 1), 0.05 g (Hgel 2), and 0.1 g (Hgel 3). The research results indicate that swelling increases as the MBA concentration decreases. This was attributed to the lower crosslinking density, which reduces the entanglement of polymer chains. Hgel 1 displayed the greatest swelling ratio 171.71 g/g, while Hgel 2 150.21 g/g and Hgel 3 144.76 g/g. The research results indicate that the swelling behavior is best described by the diffusion kinetics model, as evidenced by the best fit between the experimental data and calculations, with R² values of 0.996, 0.996, and 0.984 for Hgel 1, Hgel 2, and Hgel 3, respectively. The applicability of pseudo-second order model, in good agreement with the one found for Hgel 2 (R2 = 0.997). These results suggest that diffusion dominates the swelling behaviour and that hydrogel behaviour is sensitive to crosslinker concentration. This work highlights the potential use of chitosan-graft-poly(acrylic acid) hydrogels for sustainable applications in agriculture and biomedicine.